(untitled) - Hamrock, Bernard J. (Boston, 2005)
The second edition of Fundamentals of Machine Elements, second edition provides undergraduates and praticing engineers with a clear understanding of the theory and applications behind the fundamental concepts of machine elements. The text is rich with examples and homework problems designed to test student understanding and build their skills in analysis and design. The engineering design process is stressed throughout the book through the use of Case Studies, open-ended problems, design procedure boxes, and in-text discussion. The book is divided into two parts: Part I (chs 1-8) covers fundamental background topics, and Part II (chs 9-20), presents the design of various machine components. Unique coverage of MEMS devices is provided in chapter 20, reflecting the importance of microsystems in today's industry.
Keywords: Machine design,Mechanical movements